The Role of the Internal Audit Function in the Disclosure of Material Weaknesses - Lin, Shu; Pizzini, Mina; Vargus, Mark; Bardhan, Indranil R. (The Accounting Review, 2011)
ABSTRACT: This study investigates the role that a firm’s internal audit function (IAF) plays in the disclosure of material weaknesses reported under Section 404 of the Sarbanes-Oxley Act of 2002 (U.S. Congress 2002). Using data from 214 firms, we examine the relation between material weakness (MW) disclosures and various IAF attributes and activities. Our results indicate that MW disclosures are negatively associated with the education level of the IAF and the extent to which the IAF incorporates quality assurance techniques into fieldwork, audits activities related to financial reporting, and monitors the remediation of previously identified control problems. The timing of Section 404 work and the nature of follow-up monitoring suggests that these aspects of IAF quality help prevent MWs from occurring. We find that MW disclosures are positively associated with the IAF practice of grading audit engagements and external-internal auditor coordination, suggesting that these activities increase the effectiveness of Section 404 compliance processes.